(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
Journalistic prose, accessible to individuals with diverse educational backgrounds, resonates effectively in the realm of photojournalism. When presenting a photograph that encapsulates the essence of an event alongside informative content, it is essential to include the name and a descriptive caption beneath the photo. Whether the image features a prominent personality, a specific location, or a compelling portrait, this practice elevates factual details into meaningful and impactful information. Encountering a magazine cover image without accompanying captions for the first time often sparks surprise or prompts a page turn. Therefore, it is a lapse for the photojournalist to overlook the inclusion of a comprehensive photo description. Individuals possessing discerning skills directly engage with the visual narrative, and the absence of contextual explanation renders the invested time and effort ineffectual. The failure to provide elucidation implies a depreciation of the photographer’s meticulous work. Once a photo description is published, it stands as an immutable record, underscoring the irrevocable nature of this crucial aspect. Хураангуй. Гэрэл зураг нь сэтгүүл зүйн мэдээлэлд чухал ач холбогдол бүхий баримт байдаг. Гэтэл Монголын хэвлэл мэдээллийн хэрэгслүүд нь мэдээллийн гэрэл зурагт төдийлөн ач холбогдол өгөхгүй байгаа дүр зураг ажиглагдах болов. Иймд бид судалгааныхаа хүрээнд өдгөө эрчимтэй хөгжиж буй мэдээллийн шинэ хэрэгсэл болох сайтуудад нийтлэгдсэн мэдээллийн гэрэл зургуудад ажиглалт хийж үнэлэлт дүгнэлт өглөө. Түлхүүр үг: Фото сэтгүүлч, гэрэл зургийн сэтгүүл зүй, тайлбаргүй гэрэл зураг, агуулга, гэрэл зургийн ач холбогдол